PHYSIOLOGICAL ASPECTS OF YELLOW PASSION FRUIT WITH USE OF HYDROGEL AND MULCHING - Araújo, Danila Lima de; Souto, Antônio Gustavo de Luna; Cavalcante, Adailza Guilherme [UNESP]; Cavalcante, Lourival Ferreira; Pereira, Walter Esfrain; Melo, Alberto Soares de (FapUNIFESP (SciELO), 2022)
In the Brazilian semi-arid region, water deficit is one of the main factors that compromise the growth and productive yield of crops, including yellow passion fruit, due to the limitation of carbon assimilation by the photosynthetic activity of plants. Therefore, it is necessary to manage the soil with technologies that can reduce the loss of water in the soil and mitigate the effects of water deficit on yellow passion fruit plants cultivated under semi-arid conditions. The objective of this study was to evaluate the application of hydrogel doses and mulching to the soil on the physiological aspects of irrigated yellow passion fruit cultivation. The experiment was carried out in a randomized block design, in a 5 × 2 factorial scheme, referring to five doses of hydrogel (0.0, 0.5, 1.0, 1.5 and 2.0 g dm-3 of soil) in soil without and with mulching from signal grass (Brachiaria decumbens L.). The variables analyzed were chlorophyll indices, fluorescence (initial, maximum and variable) and gas exchange. The total chlorophyll index was increased with the application of 1.5 g dm-3 of hydrogel and the use of mulching; when applying hydrogel doses of 2.0 g dm-3 the photosynthetic rate of yellow passion fruit plants increased, whereas their transpiration rate increased with the use of mulching and doses of hydrogel; as a consequence, there was a reduction in water use efficiency.
ASPECTOS FISIOLÓGICOS DO MARACUJAZEIRO-AMARELO COM USO DE HIDROGEL E MULCHING
Keywords: Gas exchange; Mulching; Passiflora edulis L.; Water-retaining polymer